Labor Complications in Teenage and Elderly Pregnancy in Pharnomsarakarm Hospital - Maneepitaksanti, Rut (Journal of Health Science of Thailand, 2017)
The objective of this study was to compare the incidents of perinatal complications between teenage and elderly pregnancies (aged 10-19 or >35 years old) as study cases and those of the mothers aged 20-34 years old as control. The study was conducted in Pharnomsarakarm hospital during the period from October 2012 to September 2013. There were 218 cases (19.3%) of teenage pregnancy, 137 cases (12.1%) of elderly pregnancy were and 774 cases (68.6%) of the control group. It was found that teenage pregnancy had significantly higher risk for anemia than the control group; [RR (95% CI) 1.6 (1.2-2.2), p = 0.02]; whereas the elderly pregnancy group had higher risk of unusual posture of infants [RR (95% CI) 3.7 (1.5-9.2), p = 0.04)]. The results were the same in multivariate analysis with Multiple Logistic Regression.